2010
DOI: 10.3928/19404921-20100601-01
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Reiki on Anxiety, Depression, Pain, and Physiological Factors in Community-Dwelling Older Adults

Abstract: The purpose of this study was to evaluate the effect of Reiki as an alternative and complementary approach to treating community-dwelling older adults who experience pain, depression, and/or anxiety. Participants (N = 20) were randomly assigned to either an experimental or wait list control group. The pre- and posttest measures included the Hamilton Anxiety Scale, Geriatric Depression Scale-Short Form, Faces Pain Scale, and heart rate and blood pressure. The research design included an experimental component t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
60
0
8

Year Published

2013
2013
2018
2018

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 63 publications
(69 citation statements)
references
References 32 publications
1
60
0
8
Order By: Relevance
“…Primary and secondary outcomes of included phase II RCT's and pilot studies that were significant included pain (n=8 studies), quality of life, coping and health locus of control, anxiety, selfesteem, psychological distress, fatigue, joint function, depression. Five studies identified adverse effects in a minority of recipients including increased anxiety; excess energy worsening sleep or depressed mood; transient headache or crying (n=2); temporary severe pain and fever (fibromyalgia patients; n=4) (that was followed by rapid improvement in symptoms) associated with healing [13,27,28,45,53].…”
Section: Summary Of Energy Healing Interventionsmentioning
confidence: 99%
See 3 more Smart Citations
“…Primary and secondary outcomes of included phase II RCT's and pilot studies that were significant included pain (n=8 studies), quality of life, coping and health locus of control, anxiety, selfesteem, psychological distress, fatigue, joint function, depression. Five studies identified adverse effects in a minority of recipients including increased anxiety; excess energy worsening sleep or depressed mood; transient headache or crying (n=2); temporary severe pain and fever (fibromyalgia patients; n=4) (that was followed by rapid improvement in symptoms) associated with healing [13,27,28,45,53].…”
Section: Summary Of Energy Healing Interventionsmentioning
confidence: 99%
“…Utilising the same healer(s) for all sessions was a key element of 12 out of 13 studies that had significant results [12,28,29,31,32,35,37,39,43,45,49,53]. A further seven studies maintained the same healer(s) for all sessions however results of these studies were not significant [13,27,33,40,46,47,50,55].…”
Section: Key Elements Of Energy Healing Interventionsmentioning
confidence: 99%
See 2 more Smart Citations
“…Rei (sometimes thought of as a supreme being) and ki (meaning universal life energy) (Lee et al, 2008;Richeson et al, 2010;Birocco et al, 2012). Everything in the universe is made up of energy.…”
Section: Introductionmentioning
confidence: 99%